2022
DOI: 10.32535/ijabim.v7i2.1662
|View full text |Cite
|
Sign up to set email alerts
|

Online Shopping Indonesia: Customer Perception

Abstract: Online shopping has made changes in consumer behavior when shopping, especially in Indonesia, where online shopping continues to increase. For this reason, the question that arises then is how consumer perceptions are related to online shopping in Indonesia. The purpose of this study is to provide an overview of consumer perceptions of online shopping in Indonesia, namely Tokopedia, Shopee, Bukalapak and Lazada. A total of 850 respondents throughout Indonesia were involved in this study. Consumer perceptions r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…For health and care businesses, there are 37 businesses or 34.9%, fashion is 41 businesses or 38.7%, food and drink is 28 businesses or 26.4%. This finding is in accordance with the results of research by Arilaha, Fahri, & Buamonabot, ( 2021) and Bailusy, Buamonabot, Fahri, & Arilaha, (2022).…”
Section: Resultssupporting
confidence: 93%
“…For health and care businesses, there are 37 businesses or 34.9%, fashion is 41 businesses or 38.7%, food and drink is 28 businesses or 26.4%. This finding is in accordance with the results of research by Arilaha, Fahri, & Buamonabot, ( 2021) and Bailusy, Buamonabot, Fahri, & Arilaha, (2022).…”
Section: Resultssupporting
confidence: 93%
“…Regarding the personal profile of the respondents, Table 1 shows that 48% of respondents are male and 52% female, the other research showed the study, 850 people participated, and of those, 569 were women and they shop most frequently (Bailusy, 2022). About 71%, are from the age group of 18-36 years, which is generally the target market for online product sellers.…”
Section: Demographic Profilementioning
confidence: 96%
“…A new era where consumers can select the shopping media that best suits their interests in shopping has been generated by the healthy competition between traditional and online shopping. The methods used to gather product information, consumers' perceptions of risk, and their access to comparable product categories are some of the primary distinctions between the two shopping media (Bailusy et al, 2022). The Internet had revolutionized the way people shop and had quickly grown into a global phenomenon.…”
Section: Original Research Articlementioning
confidence: 99%
“…A user spends less time and effort on a basic technological system. Many customers regard Shopee as a user-friendly ecommerce platform that caters to everybody (Bailusy, Buamonabot, Fahri, & Arilaha, 2022). According to Sabeh, Husin, Kee, Baharudini, and Abdullah (2021), perceived ease of use and usefulness impact use behavior through behavioral intention.…”
Section: Literature Reviewmentioning
confidence: 99%